PENGARUH WORD OF MOUTH DAN BRAND AWARENESS TERHADAP INTENSI MENGUNJUNGI TEMPAT WISATA ZIARAH MAKAM SUNAN KALIJAGA DEMAK - Santi Ratnawati (Program Studi Ilmu Komunikasi FBIK Unissula, 2014)
Tourism is one of the largest foreign exchange earner, leveling and increase employment opportunities and incomes, strengthen unity, and unity, as well as get to know the culture of the nation. Tourism is also capable give opportunity for jobs. Thus, the optimal management is needed. As part of the delivery of information to the public, tourism can be introduced by way of word of mouth. In addition, a good impression in the minds of the public on a tourist destination, could be the trigger for the decision to visit a tourist attraction. In daily life, the decision intention to purchase a product or service is often performed as a positive information from someone else, a friend or relative you trust, or information due to the positive experiences of others previously received. The results showed that the positive information on the existence of Sunan Kalijaga will build a positive perception of the tomb of Sunan Kalijaga prospective visitor, thus building interest or intention to make a visit or re-visit. Meanwhile, a good image in the minds of potential visitors or people who have visited the grave of Sunan Kalijaga will build interest or interests that make re-visit the tomb of Sunan Kalijaga.Keywords: Tourism, Word of Mouth, Brand Awareness, intention.